Seiring dengan perkembangan Peningkatan Aktivitas Dan Hasil Belajar Tematik Dengan Menggunakan Strategi Synergetic Teaching Pada Siswa Kelas IV B SD Negeri 60 Kota Bengkulu: Peningkatan Aktivitas Dan Hasil Belajar Tematik Dengan Menggunakan Strategi Synergetic Teaching Pada Siswa Kelas IV B SD Negeri 60 Kota Bengkulu - Laras Yayas; Herman Lusa; Pebrian Tarmizi (Universitas Bengkulu, 2022)
This research is motivated by several problems that occur in the learning activities of Elementary School of 60 Bengkulu City, so that the activities and learning outcomes obtained by students have not reached the KKM that has been set. Based on observations, it is known that the passive activity of students in following the learning process and the lack of variation of teachers in using methods affect the low learning outcomes and learning activities of students. The purpose of this study is to find out the increase in activity and learning outcomes of fourth grade students B SD N 60 Bengkulu City in learning theme 9 sub-theme 1 by using Synergetic Teaching Strategy. This research included in the Classroom Action Research (CAR) which was carried out in two cycles. The results of this study indicate the average of the assessment of teacher activity observations in cycle 1, namely. 10 with the category Enough (Range 7-10). Furthermore, the results of observations in cycle II from the results of observer 1 obtained a value of 18 while the value of observer 2 obtained a value of 17. The average of the assessment of teacher activity observations in cycle 1 is. 17.5 with category Very Good ( Range 15-18 ). Furthermore, in the assessment of learning outcomes in cycle 1. the assessment of learning outcomes in Civics subjects showed the lowest score of 60. Meanwhile, the highest score was 75. Then those who scored less than 70. as many as 12 students ( 57.14% ). Meanwhile, for the range of values from 71-80, the number of students was the same, namely 4 students (19.04%). In cycle II. assessment of learning outcomes. in the Indonesian language subject, the lowest score was 70, while the highest score was 90. The number of students who scored less than 81 100 were 14 students (66.66%), then those for the 71-80 score range received the same number, namely 3 students (14.29 %), and students who scored 61-70 were 4 students ( 19.05 % ). Thus it can be concluded that there is an increase in students' thematic learning outcomes using the Synergetic Teaching strategy for grade IV B students at SD Negeri 60 Bengkulu City.